Taxonomy and Polyphasic Characterization of Alkaline Amylase Producing Marine Actinomycete Streptomyces rochei BTSS 1001 - Aparna Acharyabhatta; Siva Kumar Kandula; Ramana Terli (International Journal of Microbiology)
Actinomycetes isolated from marine sediments along the southeast coast of Bay of Bengal were investigated for amylolytic activity. Marine actinomycete BTSS 1001 producing an alkaline amylase was identified from marine sediment of Diviseema coast, Bay of Bengal. The isolate produced alkaline amylase with maximum amylolytic activity at pH 9.5 at 50°C. The organism produced white to pale grey substrate mycelium and grayish aerial mycelium with pinkish brown pigmentation. A comprehensive study of morphological, physiological parameters, cultural characteristics, and biochemical studies was performed. The presence of iso-C15 : 0, anteiso-C15 : 0, iso-C16 : 0, and anteiso-C17 : 0 as the major cellular fatty acids, LL-diaminopimelic acid as the characteristic cell wall component, and menaquinones MK-9H(6) and MK-9H(8) as the major isoprenoid quinones is attributed to the strain BTSS 1001 belonging to the genus Streptomyces. Comparison of 16S rRNA gene sequences showed that strain BTSS 1001 exhibited the highest similarities to the type strains of Streptomyces rochei (99%), Streptomyces plicatus (99%), and Streptomyces enissocaesilis (99%). Using the polyphasic taxonomical approach and phenotypic characteristic studies, the isolate BTSS 1001 was characterized as marine actinomycete Streptomyces rochei.